CURRENT PERSPECTIVE IN VENTILATOR ASSOCIATED PNEUMONIA AND ITS MANAGEMENT (World Bulletin of Public Health, 2025)
The use of Meropenem combined with Aztreonam antibacterial therapy for ventilator-associated pneumonia has a positive effect in the decrease in the duration of artificial ventilation and there was a reduction in length of stay in the intensive care unit [ICU], hence reducing cost of treatment, and with lower mortality rate as compared to the group that used traditional antibiotics. Is important to note this definitions, recurrence of VAP means: there is initial recovery after 8 days of antibiotic therapy with subsequent repeated manifestation of VAP. Superinfection: This is initial recovery after 8 days of antibiotic therapy with subsequent repeated manifestation of VAP, caused by completely different pathogens.
Keywords: lungs; combination of drugs; Aztreonam